2012
DOI: 10.1080/14685248.2012.696118
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent nature of the atmospheric boundary layer and its impact on the wind energy conversion process

Abstract: Wind turbines operate in the atmospheric boundary layer, where they are exposed to the turbulent atmospheric flows. As the response time of wind turbine is typically in the range of seconds, they are affected by the small scale intermittent properties of the turbulent wind. Consequently, basic features which are known for small-scale homogeneous isotropic turbulence, and in particular the well-known intermittency problem, have an important impact on the wind energy conversion process. We report on basic resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…With the turbu lence taken into account, better correlation of the results at the deceleration point is obtained; however, full agreement with our data is not observed. This important question needs separate detailed consider ation first of all due to the specifics of the effect the atmospheric turbulence has on large scale obstacles [13] as compared with artificially generated pulsations of velocity in wind tunnels.…”
Section: Experimental Results and Their Discussionmentioning
confidence: 99%
“…With the turbu lence taken into account, better correlation of the results at the deceleration point is obtained; however, full agreement with our data is not observed. This important question needs separate detailed consider ation first of all due to the specifics of the effect the atmospheric turbulence has on large scale obstacles [13] as compared with artificially generated pulsations of velocity in wind tunnels.…”
Section: Experimental Results and Their Discussionmentioning
confidence: 99%
“…[9][10][11] Mücke et al [12] demonstrated the correlation of extreme events in atmospheric wind fields with the load alternation on the turbine blade and main shaft. The follow-up research by Wachter et al [13] showed the strong intermittent statistics of wind fluctuation and its impact on intermittent characteristics in the wind energy conversion process. Recently, the variation of wind loads on blades, tower and rotor at different atmospheric conditions have been systematically studied by Sathe et al [14] Their results also showed different influences of wind profiles and turbulence on the loads under diabatic conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Intermittent statistics have a big impact on the wind energy conversion process, 9 as extreme wind gusts lead to heavy fluctuations in mechanical loads. These turbulence induced load fluctuations are considered to increase wind turbine failure rates 8 and are heavily underestimated by Gaussian statistics based industry standards.…”
Section: Introductionmentioning
confidence: 99%